Improving memory for unusual events with wakeful reactivation - Glicksohn, Arit; Shams, Ladan; Seitz, Aaron R. (Frontiers in Psychology, 2023)
Memory consists of multiple processes, from encoding information, consolidating it into short- and long- term memory, and later retrieving relevant information. There is evidence suggesting that multisensory encoding improves later retrieval of the unisensory details of these memories, such as better remembering images previously presented with sounds. One possible mechanism is the formation of rich multisensory representations, later activated by unisensory stimuli. Recent work also suggests that replaying unisensory cues during a consolidation phase, such as sounds or odors, improves memory for objects in the presence of these cues. We explore here the possibility that reactivation of a multisensory representation leads to better memory for all its unisensory components. A single reactivation during wakefulness is likely to be potent for events that are particularly memorable or salient. We presented participants with everyday objects, and ‘tagged’ these objects with sounds (e.g., animals and their matching sounds) at different screen locations. ‘Oddballs’ were created by presenting unusual objects and sounds (e.g., a unicorn with a heartbeat sound). During a short ‘reactivation’ phase, sounds of normal and oddball objects were replayed in succession. Participants were then tested on their memory for visual and spatial information in the absence of sounds. Participants were better at remembering the oddball objects compared to normal ones. Importantly, participants were also better at recalling the locations of oddball objects whose sounds were replayed compared to objects whose sounds that were not presented again. These results suggest that episodic memory benefits from associating objects with salient cues, and that reactivating those cues strengthen the entire multisensory representation, resulting in enhanced memory for unisensory attributes.